Qualitative data analysis a methods sourcebook - Miles, Matthew B.; Huberman, A. Michael; Saldana, Johnny (SAGE, 2014)
The Third Edition of Miles & Huberman's classic research methods text is updated and streamlined by Johnny Salda a, author of The Coding Manual for Qualitative Researchers. Several of the data display strategies from previous editions are now presented in re-envisioned and reorganized formats to enhance reader accessibility and comprehension. The..